Edukasi Deteksi Dini Kanker Payudara kepada Ibu PKK di Desa Sudimara Kecamatan Cilongok - Doni Febriana Setiawan; Atun Raudatul Ma’rifah; Murniati Murniati (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Breast cancer (carcinoma mammae) is a malignant tumor that grows in breast tissue. This cancer begins in the mammary glands, fatty tissue, and connective tissue of the breast. The incidence of breast cancer in Indonesia has reached 42.1 cases per 100,000 population, with a death rate of 17 per 100,000 population. Sudimara Village has the highest number of women diagnosed with breast cancer in Cilongok District, with 13 cases, including 2 deaths, between 2022 and 2024. Several factors can influence breast cancer, including age, lifestyle, genetics, drastic weight gain or loss, and the environment. This Community Service (PKM) activity was attended by 28 women from the Family Welfare Movement (PKK). The pre-test and post-test results showed an increase in the average score, from 52.6 to 86.4. This activity was conducted using lecture and discussion methods, using PowerPoint presentations and leaflets as media, and featured a video demonstration of how to perform BSE. This outreach activity demonstrated increased knowledge among PKK women regarding early breast cancer detection.